Insulin resistance, beta-cell function, adipokine profiles and cardiometabolic risk factors among Chinese youth with isolated impaired fasting glucose versus impaired glucose tolerance: the BCAMS study. Issue 1 (10th February 2020) - Li, Yu; Feng, Dan; Esangbedo, Issy C; Zhao, Yanglu; Han, Lanwen; Zhu, Yingna; Fu, Junling; Li, Ge; Wang, Dongmei; Wang, Yonghui; Li, Ming; Gao, Shan; et al.
Abstract : Objective: Impaired fasting glucose (IFG) and impaired glucose tolerance (IGT) may convey disparate risks of metabolic consequences. Fasting plasma glucose (FPG), while an expedient screening procedure, may not adequately assess metabolic risk, particularly among youths. In order to inform a strategy for screening Chinese youth for pre-diabetes, we examined the relative value of IFG versus IGT to define metabolic risk by assessing their association with insulin resistance, beta-cell dysfunction, adverse adipokine profiles and other cardiometabolic risk factors. Research design and methods: We recruited 542 subjects (age 14–28 years) from the Beijing Child and Adolescent Metabolic Syndrome study for an in-depth assessment of cardiometabolic risk factors, including a 2-hour oral glucose tolerance test, liver ultrasound and serum levels of four adipokines. Results: FPG failed to identify nearly all (32/33) youths with IGT, whereas 2-hour plasma glucose (2 h PG) missed 80.8% (21/26) of subjects with IFG. Impaired beta-cell function was evident from decreased oral disposition indices in those with isolated impaired fasting glucose (iIFG) or isolated impaired glucose tolerance (iIGT) versus normal glucose tolerance (NGT) (all p<0.001), whereas reduced insulin sensitivity (Matsuda) index was most pronounced in the iIGT group (p<0.01). Moreover, alterations in adipokine levels (fibroblast growth factor 21, adiponectin and leptin/adiponectin ratio) were associated with iIGT (p<0.05) but not iIFG. Youths with iIGT had a 2-fold to 32-fold increased incidence of hypertriglyceridemia, hypertension and metabolic syndrome (MetS) compared with those with NGT. In addition, subgroup analyses of participants with normal FPG revealed that the odds of having IGT increased 3-fold to 18-fold among those with elevated TGs, hypertension, moderate-to-severe non-alcoholic fatty liver disease or MetS. Conclusions: Chinese youth with iIGT exhibit a higher cardiometabolic risk profile than those with iIFG. Thus, 2 h PG is preferred over FPG to identify the pre-diabetes phenotype at greatest risk of subsequent development of cardiovascular disease. Trial registration number: NCT03421444 .